Low Velocity Impact Behavior of Glass Filled Fiber-Reinforced Thermoplastic Engine Components - Mouti, Zakaria; Westwood, Keith; Kayvantash, Kambiz; Njuguna, James A. K. (MDPI, 2010)
This paper concerns automotive parts located underneath the engine and in particular the engine oil pan. Classically made of stamped steel or cast aluminum, new developments have allowed the manufacture oil pans with polyamide 66 reinforced by 35% weight of short glass fiber. However, polyamides have some limitations and the most significant is their response to localized impact loading. The nature of the impact considered here is of a typical stone collected from the road and projected into the oil pan. Low velocity impact investigations were carried out using a gas gun and drop weight tower. The study shows that the design of the oil pan has a significant contribution in the shock absorption. In addition to the material properties, the geometry and the ribbing both cleverly combined, increase the impact resistance of the component significantly. Areas of oil pan design improvement have been identified and conclusions drawn.